Smart apps creator-based media to enhance addition and subtraction learning outcomes - Herliana, Yunika; Witanto, Yuli (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to develop, validate, and evaluate an interactive learning media based on Smart Apps Creator (SAC) to improve second-grade elementary students’ learning outcomes in addition and subtraction. Method: A Research and Development (R&D) approach was applied using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The media was implemented in a real classroom setting involving 29 second-grade students from SD Labschool UNNES. Data were collected through expert validation, pretest-posttest assessments, and student-teacher response questionnaires. Data analysis included descriptive statistics, paired sample t-tests, and N-Gain analysis. Findings: The SAC-based media achieved high feasibility ratings from both media (92.6%) and material (89.2%) experts. Student and teacher responses rated the media as “very feasible.” Statistically significant improvements were observed between pretest and posttest results (p < .001), with a high N-Gain score of 0.79. These results indicate that the media effectively enhanced students’ mastery of addition and subtraction. Significance: This study provides empirical evidence supporting the use of SAC-based interactive learning media as an effective tool for early mathematics instruction. The media not only improves cognitive outcomes but also promotes engagement and motivation among young learners. These findings underscore the potential of SAC-based tools to enrich classroom instruction and contribute to the advancement of technology-integrated learning in elementary education.